The Application of Choice-Based Conjoint Model to Study Government Authorities Preference: A Case of Traffic-Subsidy-Pollution Related Policy in Indonesia - Gudono Gudono (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2010)
According to the UN, air pollution kills more than 3 millionpeople each year (UN-Habitat 2007). Despite the magnitude ofthe impact, delays in making decisions about the environmentare quite common among governments worldwide. The purposesof this study are twofold. First, the study is to investigate therelative strength of attributes of environmental policy such asmethods of vehicle restriction, percentage of reduction in lead (and CO2) content, and percentage of subsidy reduction. Second, the study is to test government choice when it facesconservative, “scientific,” and popular policy alternatives. Toachieve both objectives this research uses an experimentalmethod. The orthogonal design is adopted for stimuli presenta-tion and conjoint analysis is used for data analysis. The re-search participants are students of an accounting graduateprogram of a state university in Java (Indonesia).The results suggest CO2/lead reduction has the strongesteffect on policy maker preference. In addition, those policymakers tend to prefer the status quo condition which indicatesconservative views. This is demonstrated by the tendency of theirchoice on an alternative policy package which requires minimum changes compared with the existing policies (a maximumutility of 64.3 percent vs. 28.6 percent and 7.1 percent of otheralternatives). In addition, bureaucrats tend to play “safe”(namely the reduction of lead content in gasoline) when thepossibility of resistance is imminence. Some consequences of theresearch findings are also discussed. Keywords: conjoint analysis; mixed environmental; public policy; utility function